Incomplete enforcement of pollution regulation : bargaining power of Chinese factories - Wang, Hua (Policy research working paper, 2002)
In dealing with local environmental authorities, Chinese firms facing adverse financial situations have more bargaining power than other firms, while those generating more complaints from the public about their emissions have less